2014
DOI: 10.1080/01446193.2014.938670
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the adoption of innovative products on Australian road infrastructure projects

Abstract: Construction product innovation can exert a positive influence on project and industry performance. However, guidance is scarce on product innovation diffusion for road infrastructure, in contrast to the large body of literature on the manufacturing industry. A conceptual framework is proposed to understand these processes. Advice is given to managers based on the framework and a large quantitative survey. The framework focuses on contextual characteristics that influence the decision to adopt new-to-industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(80 reference statements)
2
17
0
Order By: Relevance
“…Hartmann’s (2006) interviewees mentioned that there had to be a clearly visible added value for an (external) client, given the additional costs and risks associated with the innovation. Rose and Manley (2014) in their Australian study of road infrastructure project innovations also found that disagreements about risk allocation for new product failure were a major obstacle to innovation. For creating a sustainable built environment and exploiting the opportunities of engaging financial stakeholders (Lützkendorf et al ., 2011), it must be recognized that these are risk-conscious, and they may still lack the necessary practical experience of the reliability as well as the costs of construction and usage for new sustainable technologies.…”
Section: Technology Risks and Costly Signallingmentioning
confidence: 99%
“…Hartmann’s (2006) interviewees mentioned that there had to be a clearly visible added value for an (external) client, given the additional costs and risks associated with the innovation. Rose and Manley (2014) in their Australian study of road infrastructure project innovations also found that disagreements about risk allocation for new product failure were a major obstacle to innovation. For creating a sustainable built environment and exploiting the opportunities of engaging financial stakeholders (Lützkendorf et al ., 2011), it must be recognized that these are risk-conscious, and they may still lack the necessary practical experience of the reliability as well as the costs of construction and usage for new sustainable technologies.…”
Section: Technology Risks and Costly Signallingmentioning
confidence: 99%
“…Thus, the fragmentation between project-actors and difficulties in coordinating actors are considered to hamper innovation in the construction context (Egan 1998, Dulaimi et al 2002. Moreover, construction is a heavily regulated environment that is suggested to inhibit innovative solutions in projects (Hartmann 2006, Rose andManley 2014).…”
Section: Literature Overviewmentioning
confidence: 99%
“…It was suggested that opportunism moderates commitment. There is much that catalogues the adversarial nature of the construction industry; for example, a review of the Scopus database identified several examples (e.g., Boukendour and Hughes 2014;Eriksson 2010;Rose and Manley 2014;Smiley et al 2014).…”
Section: Commitmentmentioning
confidence: 99%